Management of Arabic Language Instruction Using the Love-Based Curriculum (LBC) Approach at State Islamic Senior High School - Reni Dwita Putri; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
Despite the growing scholarly interest in the Love-Based Curriculum (LBC), empirical research examining its implementation in Arabic language instruction remains limited. Most existing studies have discussed LBC from conceptual and general educational perspectives, leaving its practical application in language learning contexts underexplored. This study investigates the management of Arabic language learning through the LBC approach at State Islamic Senior High School, a state Islamic senior high school in Riau Province, Indonesia. Employing a qualitative descriptive design, data were collected through observations, interviews, and documentation involving two Arabic language teachers and two Grade XI students selected purposively. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the LBC approach fosters harmonious, humanistic, and dialogic teacher–student relationships; promotes positive character traits such as discipline, responsibility, empathy, and religiosity; and facilitates the internalization of spiritual, social, and moral values through Qur’anic integration, religious routines, and humanistic classroom practices. The study further demonstrates that character development occurs through supportive emotional relationships and meaningful value-based learning experiences. This research contributes to the field of Arabic language education by providing empirical evidence that the Love-Based Curriculum can serve as an effective instructional management framework that integrates linguistic learning, character formation, and spiritual development within an Islamic secondary school context.